Dampak Beban Kerja Terhadap Kinerja Karyawan Dannis Collection Surabaya - Purnasari, Esti; Mahmudah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of workload on employee performance at Dennis Collection Surabaya. The research approach used is quantitative, with data collected through questionnaires distributed to 62 employees of Dennis Collection, and the data were analyzed using simple linear regression analysis. The results show a positive and significant relationship between workload and employee performance, with a contribution of 37.6 percent. This indicates that the increase in workload at Dennis Collection is significantly related to the improvement in employee performance. These findings highlight the importance of effective workload management in enhancing employee performance and maintaining their well-being, such as through appropriate workload balancing strategies, providing adequate resources, and offering suitable rewards to maintain employee motivation and performance. These findings make an important contribution to the human resource management literature and offer practical recommendations for managing workload in a dynamic work environment. Additionally, they provide a framework for more effective management strategies in the future. Therefore, it is crucial for Dennis Collection to continuously monitor and adjust employee workloads to ensure they remain within reasonable limits and support the balance between work demands and employee well-being.